2015
DOI: 10.1016/j.actamat.2014.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution of charged defects in the fatigue process of polycrystalline BiFeO3 thin films

Abstract: Fatigue failure in ferroelectrics has been intensively investigated in the past few decades. Most of the mechanisms discussed for ferroelectric fatigue have been built on the "hypothesis of variation in charged defects", which however are rarely evidenced by experimental observation. Here, using a combination of complex impedance spectra techniques, piezoresponse force microscopy and first-principles theory, we examine the microscopic evolution and redistribution of charged defects during the electrical cyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…PFM is the primary tool to investigate the nanoscale ferroelectric domains and polarization dynamics for various piezoelectric and ferroelectric materials such as PZT, relaxor‐based piezoelectric materials (PZN‐PT or PMN‐PT), multiferroic BiFeO 3 (BFO) and organic ferroelectrics. We have applied PFM in many material systems, including doped/undoped BFO thin films, PZN‐PT single crystal, CH 3 NH 3 PbI 3 perovskite, MOF nanocrystals, poly(vinylidene fluoride) (PVDF) film, and ferroelectric‐like copper‐doped zinc oxide (ZnO:Cu) thin films . Taking the PZN‐PT single crystal as an example, the out‐of‐plan domain structure and the corresponding surface potential are illustrated in Figure i.…”
Section: Examples Of Materials Systems Investigated Using Spm Techniquesmentioning
confidence: 99%
“…PFM is the primary tool to investigate the nanoscale ferroelectric domains and polarization dynamics for various piezoelectric and ferroelectric materials such as PZT, relaxor‐based piezoelectric materials (PZN‐PT or PMN‐PT), multiferroic BiFeO 3 (BFO) and organic ferroelectrics. We have applied PFM in many material systems, including doped/undoped BFO thin films, PZN‐PT single crystal, CH 3 NH 3 PbI 3 perovskite, MOF nanocrystals, poly(vinylidene fluoride) (PVDF) film, and ferroelectric‐like copper‐doped zinc oxide (ZnO:Cu) thin films . Taking the PZN‐PT single crystal as an example, the out‐of‐plan domain structure and the corresponding surface potential are illustrated in Figure i.…”
Section: Examples Of Materials Systems Investigated Using Spm Techniquesmentioning
confidence: 99%
“…''tail to tail'' domain wall is negatively charged domain wall, and the ''head to head'' is positively charged domain wall. Charged domain walls show metallic behavior and are correlated with the polarity of the majority carriers [53]. Thus, the majority carriers including positively charged hole or V ÁÁ O assemble on ''tail to tail'' domain wall in p-type BiFeO 3 system [54,55] and result in the increase of leakage current of BFO thin films with ''tail to tail'' domain walls.…”
Section: Ohimic Conductionmentioning
confidence: 98%
“…20 Ke, et al discussed the microstructural evolution of charged defects during the electrical cycling in Bi Fe O 3 thin films. 21 According to the mentioned references it is found that most of them focused on the metal films due to cyclic loads. Herein, we finished the low-cycle fatigue of polmeric thin films.…”
Section: Article Scitationorg/journal/advmentioning
confidence: 99%